Role of Chromosomal Instability in Cancer – An Update - Dr. K. Ramesh Reddy (Asian Journal of Pharmaceutics (AJP), 2025)
Chromosomal instability (CIN) is a type of genomic instability in which chromosomes are unstable such that either whole or part of chromosomes are deleted or duplicated. CIN is caused by failures in chromosome errors, such as abnormalities in the machinery involved in chromosomal segregation, such as spindle assembly checkpoints, centrosome amplification, incorrect microtubule-kinetochore attachments, or faulty sister chromatid cohesion. CIN is detrimental to healthy cells and is associated with decline, altered metabolism, proteotoxic stress, cell cycle arrest, and DNA damage. CIN is a prevalent characteristic of solid tumors, a prospective therapeutic target for cancer treatment. It plays a significant role in both the development of tumors and the way they respond to treatment. CIN promotes the accumulation of mutations that result in aggressiveness or drug-resistant phenotype. CIN could empower the tumors with increased adaptation capabilities, facilitating adaptive resistance to therapies. Identifying the intricate structure of CIN is essential to comprehending the processes of tumorigenesis as well as producing potent anti-tumor therapies. A description of CIN’s effects and causes is given in this review; experts still remain perplexed by the phenomenon’s contradictory nature. The prospect of CIN-based anti- cancer treatment is finally examined in this article.